2020
DOI: 10.1021/acs.jchemed.9b01056
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Context on Stoichiometry Conceptual and Algorithmic Subject Matter Knowledge among South African Physical Sciences Teachers

Abstract: Teachers’ conceptual subject matter knowledge of stoichiometry is a global concern. Such knowledge is contextually dependent, as is the feasibility of attaining particular outcomes during in-service teacher education workshops. In an attempt to understand what is feasible in various contexts, I explore the relationships between South African physical sciences teachers’ environments, education, and teaching experience and their possession of, and ease with which they learn, various types of stoichiometry knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Mismatch between successful application of mole-related equivalence within calculation and conceptual questions. The findings given in Stott (2020) are related to those discussed in this article, since they refer to the same data set resulting from the same series of interventions. These showed that improvement for various categories of conceptual knowledge across the intervention was context dependent.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Mismatch between successful application of mole-related equivalence within calculation and conceptual questions. The findings given in Stott (2020) are related to those discussed in this article, since they refer to the same data set resulting from the same series of interventions. These showed that improvement for various categories of conceptual knowledge across the intervention was context dependent.…”
Section: Discussionmentioning
confidence: 80%
“…The pre-and post-tests each contained sixteen multiple choice questions which were identical between the tests, and four calculation questions which differed slightly between the tests, although the difficulty (Horvat et al, 2016) and complexity (Knaus et al, 2011) levels of corresponding questions are considered comparable, as indicated in Appendix B. The multiple choice questions have been given, justified and analysed, in Stott (2020). Two of these questions measured algorithmic manipulation rather than conceptual understanding, and so have been excluded from this study.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the only key factor that affects teaching and learning for concept development is finding out what is known to students before each instruction so formation of alternative concepts can be avoided (Hanson, 2016). According to Ausubel's theory of meaningful learning (Stott, 2020), instructions 48…”
Section: Discussionmentioning
confidence: 99%
“…Then, students are guided to find new concepts in the investigation stage by engaging them directly in a practicum or by giving them concrete data so they can analyze such data and discover new concepts. According to (Stott, 2020), instructions that provide facts on the interconnection between one concept and another can promote conceptual understanding. After students' understanding is formed, the students are taken to a problem in the guided-connection stage, so it can be discovered whether the concepts formed can be applied correctly by the students in solving problems and it can be ensured that no alternative concepts are used by the students in their problem-solving activity.…”
Section: Discussionmentioning
confidence: 99%